A Study on inventory management for fast moving goods - Çınar, Kazım Taner (My University, 1999)
A STUDY ON INVENTORY MANAGEMENT FOR FAST MOVING GOODS SUMMARY Inventory may be the highest cost of investment in the firm. Too many inventories lead to excess stock and the possibility of obsolescence and deterioration. On the other hand, if the inventory is too low, the service level suffers and customers may begin to purchase from competitive firms. A proper balance between inventory investment and service level is necessary. The common goal is always to have only the amount of inventories that is efficient and economical. As inventory levels can affect both profit and investment, inventory management is one of the main issues to determine how successful is the management of a company. There are many ways and countless approaches for inventory management. Besides some quantitative studies, an inventory manager should also be in charge of qualitative analysis. Unfortunately, there are no basic rules to reach absolute success even all of them are totally applied. General mathematical concepts are, of course, valid but the most important issue is to know the environment in which a special inventory management program is used. In this study, I analyzed a system that I know very well. I created an inventory management model. I had to neglect some points that do not affect the business directly and frequently. I mentioned almost all-internal and external concepts that an inventory manager should take into consideration. The study is divided into 4 chapters. The way of preparing these chapters base on the following concepts: i. showing a general view about the aim of the study and inventory basics ii. designing the model, putting forward the problem and offering a solution First and second chapters focus on the general concepts of the study itself and also inventory. A short part is also prepared to give an idea about the inventory control history. Management function on inventory control is stressed to show that decision making is important. Products themselves and the financial consideration are important issues to affect inventory control. The solution offered in this study depends on the definitions, approaches and processes that are mentioned in chapter 2. Third chapter is the heart of the study that focuses on the model. The model is described and the problem is brought up. The branches of the model, attachment of forecasting, solutions suggestions are all described in this chapter. The biggest advantage of the model is to rely on real data and to see the output of the designed process. In the study, I used some general inventory management tools to reach concrete mathematical results and the outline in my model can be summarized step by step like below: 1. Forecasting the target quantity of month 2. Forecasting average unit price of month 3. Forecasting profit margin of month 4. Determining revenue target of month 5. Determining profit target of month 6. Determining lead time 7. Determining safety stock days and level 8. Forecasting the demand in the period of lead time 9. Determining order point (order point is the inventory amount which is equal to the sum of safety stock level and the demand in the period of lead time 10. Forecasting the demand between the first and last arrival of goods 11. Replacing order 12. Repeat from 8 to 11 13. Checking sales target realizations at the end of the month 14. Checking run rate realization 15. Comment This study can be developed in both quantitative and qualitative ways. I also put forward some points in the last chapter to lead the people who probably study on this topic in the future. In conclusion, my study can be used as a reference guide to give an idea how to build up an inventory control system. The most important point is that every business environment should be analyzed independently afterwards -according to the model of the business- mathematical solutions can be integrated. HIZLI DÖNÜŞÜMLÜ ÜRÜNLER İÇİN BİR STOK YÖNETİMİ ÇALIŞMASI

Bir firmanın en yüksek maliyetli yatırımı stoğu olabilir. Optimum düzeyin üzerindeki fazla stok piyasa şartlarına göre eskir ve değerini yitirir. Bunun yanında düşük seviyedeki stok ise servis kalitesini düşürür ve müşterilerin rakip firmalara yönelmesine yol açar. Bu nedenle stoğa yapılan yatırım ile servis düzeyi arasında tam bir denge olması gerekir. Genel amaç etkili ve düşük maliyetli stoğa sahip olmaktır. Stok yönetimine ilişkin pekçok yöntem ve yaklaşım vardır. Stok yönetimi yapanların, sayısal çalışmaların dışında nitelik analizleri yapması da gerekmektedir. Herşeye rağmen bütün stok yönetimi araçları kullanılsa bile kesin başarıya ulşatıracak kurallardan söz etmek olası değildir. Stok yönetiminde, hiç şüphesiz, genel kabul görmüş matematik kavramları uygulanabilir ancak en önemli nokta stok yönetimine maruz kalan işi iyi bilmek ve doğru stok yönetimi programını uygulamaktır. Tez çalışmamda çok iyi tanıdığım bir sistemi analiz ettim ve bir stok yönetimi modeli tasarladım. Bu modelde, işi doğrudan etkilemeyen ya da etkilese bile sıklıkla etkilemeyen bazı etmenleri göz ardı ettim. Bununla birlikte stok yönetimi için mutlaka değerlendirilmesi gereken iç ve dış şartları da belirttim. Dört bölümden oluşan bu çalışma hazırlanırken iki temelden hareket edilmiştir: i. çalışmanın amacı ve stok kavramının genel olarak tanımlanması ii. üzerinde çalışılan problemin ortaya atılması ve uygun modelin tasarlanması İlk iki bölümde çalışma ve stokla ilgili genel kavramlar aktarılmıştır. Stok kontrol yöntemlerinin tarihi hakkında kısa bilgilendirme yapılmış, stok kontrolünde yönetimin önemine değinilmiş, ürünlerin ve finansal etmenlerin stok yönetimini etkileyen en önemli kriterler olduğu belirtilmiştir. Ortaya atılan model ve çözüm önerilerinin tamamı ikinci bölümdeki tanımlar, yaklaşımlar ve yöntemlere dayanmaktadır. Kullanılan modelin tasarlanıp anlatıldığı üçüncü bölüm çalışmanın kalbi niteliğindedir. Model taslağı, bölümleri, tahmin yöntemleri, çözüm önerileri bu bölümde yer almaktadır. Modelin en önemli avantajı gerçek verilerin kullanılması ve izlenen yönteme ait sonuçların görülebilmesine verdiği olanaktır. Çalışmada yer alan model maddeler halinde aşağıdaki gibi özetlenebilir: 1. Aylık satış adedi tahmini yapmak 2. Aylık ortalama birim fiyat tahmini yapmak 3. Aylık kar oranı tahmini yapmak 4. Aylık satış cirosu hedefi belirlemek 5. Aylık satış karı hedefi belirlemek 6. Ürün ulaşım süresini (lead time) belirlemek 7. Emniyet stok için gün adedini ve stok düzeyini belirlemek 8. Ürün ulaşım süresi (lead time) için talep tahmini yapmak 9. Sipariş verme noktasını belirlemek 10. İlk ve bir sonraki siparişler arasındaki talebi belirlemek 11. Sipariş vermek 12. 8'den 11'e yöntemi tekrar uygulamak 13. Ay sonunda satış hedeflerine ulaşılıp ulaşılmadığını kontrol etmek 14. Dönüş hızı gerçekleşmelerini kontrol etmek 15. Yorum yapıp raporlamak Bu çalışma farklı nicel ve nitel yollarla geliştirilmeye açıktır. İlerde yapılabilecek başka çalışmalara ışık tutması için son bölümde bazı yönlendirmeler de yapılmıştır. Sonuç olarak tez çalışmam stok kontrol sistemleri oluşturacaklara fikir verebilecek bir tür referans rehber olarak kullanılabilir. Buradaki en önemli nokta her iş ortamının kendine özgü şartlar içinde analiz edilmesi ve ona uygun modellerin tasarlanmasıdır.
Keywords: İŞLETME - MALİYET YÖNETİMİ